Analisis Sistem Penjadwalan Perawatan Mesin Penggiling Kedelai pada UMKM Tahu Wijaya - Arista, Anggia; Sumbara, Syah Fery Zaki; Azharman, Zefri (SURYA TEKNIKA, 2025)
Tahu Wijaya, a micro, small, and medium enterprise (MSME), relies on soybean grinding machines as the main equipment in its production process. However, the high frequency of machine failures results in recurring downtime, thereby disrupting production continuity. This study aims to determine an optimal maintenance schedule for the soybean grinding machines to minimize downtime and improve production efficiency. The method used in this study is Reliability Centered Maintenance (RCM), beginning with the collection of primary data through observation, interviews, and questionnaires, along with secondary data from machine downtime records. Risk analysis of machine failures was conducted using the Failure Mode and Effect Analysis (FMEA) method to obtain the Risk Priority Number (RPN) for each machine component. The results showed that the grinding stone was the component with the highest RPN of 256, followed by the motor with 168 and the adjustment bolt with 150. Additionally, the calculations of Mean Time to Failure (MTTF) and Mean Time to Repair (MTTR) yielded values of 22.55 hours and 1.5 hours, respectively. Based on these analyses, the ideal preventive maintenance interval was established before the machine reached 244 operating hours. This study concludes that the application of the RCM method is effective in producing a data-driven machine maintenance schedule that reduces potential downtime, thereby supporting smooth and continuous production at Tahu Wijaya MSME